Sectoral determinants of foreign affiliate sales - Eddy Bekkers; Indre Macskasi (Johannes Kepler University of Linz, Department of Economics, 2015)
We test recent theories on sectoral determinants of foreign affiliate sales employing European foreign affiliate sales statistics (FATS). On the one hand, we test hypotheses by Oldenski (2012) that foreign affiliate sales are less likely in sectors with complex tasks and more likely in sectors where communication with customers is important. On the other hand, we test the hypothesis by Keller and Yeaple (2013) that the force of gravity is stronger in more complex sectors. Employing Poisson and Negative Binomial estimators, we find support for the hypotheses in Oldenski (2012) and contradict the hypothesis in Keller and Yeaple (2013).
Keywords: F23; 330; Affiliate Sales; European Affiliate Sales Data; Task Complexity; Communication with Customers; Gravity of Knowledge